Safety and tolerability of Fingolimod in Latin american patients with relapsing-remitting multiple sclerosis: the open-label FIRST LATAM study. - Ordoñez-Boschetti, Laura (2015)
Introduction: Fingolimod 0.5 mg is an orally active sphingosine 1-phosphate receptor modulator approved for use in adults with relapsing multiple sclerosis (MS). The efficacy and safety profile of fingolimod has been well characterized in a large clinical development program. Here, we report the safety and tolerability of fingolimod in relapsing-remitting MS (RRMS) patients from Latin America. Methods: A total of 162 patients with RRMS, predominantly from Latin American countries (138/162), were enrolled in this 16-week, single treatment arm, open-label, multi-center study. Unlike the phase III pivotal studies, this study permitted enrollment of patients with controlled diabetes, certain cardiac and pulmonary conditions, older age, and higher baseline Expanded Disability Status Scale. All patients were monitored clinically for a minimum of 6 hours after the first dose. Safety and tolerability assessments were based on adverse events, clinically notable laboratory abnormalities, vital signs, ophthalmic examinations, and electrocardiograms. Results: Overall, the safety and tolerability profile was consistent with that reported previously in phase 3 studies and the FIRST study. Adverse events (AEs) were predominantly mild (n = 49, 35.5%) or moderate (n = 27, 19.6%). Three patients (2.2%) discontinued fingolimod due to AEs. Infections were reported in 33 patients (23.9%) and were predominantly mild in nature (n = 28, 20.3%). Increases in alanine aminotransferase enzymes of ≥3, ≥5 and ≥10 upper limit of normal were reported in five (3.7%), three (2.2%) and one (0.7%) patients, respectively. Hypertension cases (n = 3; 2.2%) did not result in treatment discontinuation and were controlled with antihypertensive therapy. Following first-dose administration, the majority of patients (90.6%) were discharged at 6 h. During the first-dose monitoring, 5 cases of bradycardia were reported; none required extended monitoring or treatment for symptomatic bradycardia. Conclusion: The first dose of fingolimod 0.5 mg was well tolerated in RRMS patients from Latin America. The overall safety profile was clinically manageable and consistent with previous fingolimod studies.